The Antecedents Of Leader-Member-Exchange (LMX) Relationships In African Context: The Influence Of The Supervisor’s Feedback Delivery-Tactic - ALO, OBINNA; Ahmad, Arslan (My University, 2022)
Purpose The current paper aims to analyse the antecedents of leader–member exchange relationships (LMX) by specifically focusing on the influence of the supervisor’s feedback delivery tactic. Design/methodology/approach This study uses qualitative research methods with primary interviews as the main data source. Primary interviews with 40 managers from top supermarkets in Nigeria, South Africa and the UK were undertaken. Findings The authors found that both high-quality positive feedback and constructive criticisms produced the same feelings – more positive interpersonal relationships with their supervisors, higher levels of commitment to their organisations, higher job satisfaction and thus, high-quality LMX relationships. Where criticisms were delivered without greater interpersonal treatment, feedback was perceived as negative, and participants revealed lack of job satisfaction, lack of commitment to their organisations, poor interpersonal relationship with their supervisors, high turnover intent and thus low-quality LMX relationship. Originality/value To the best of the authors’ knowledge, the current paper is one of the first studies to highlight the consequences of different feedback delivery tactics on subsequent LMX quality particularly in African context. The authors specifically develop a process-based model of enhancing high-quality LMX, which shows the role of the supervisor’s feedback delivery tactic in the process. The authors also develop a process-based model that illustrates how negative/unconstructive feedback could result in a low-quality LMX. Finally, to the best of the authors’ knowledge, this paper is also one of the first to offer a comparative assessment between African and British (the UK) empirical settings and highlight some interesting dynamics concerning LMX quality and role of supervisor’s feedback delivery tactic.
Keywords: Leader-member exchange (LMX); united kingdom; feedback